2017
DOI: 10.1177/1176934317697978
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Categorize 2-Dimensional Patterns Using Statistics of Spatial Organization

Abstract: We developed a measurement framework of spatial organization to categorize 2-dimensional patterns from 2 multiscalar biological architectures. We propose that underlying shapes of biological entities can be approached using the statistical concept of degrees of freedom, defining it through expansion of area variability in a pattern. To help scope this suggestion, we developed a mathematical argument recognizing the deep foundations of area variability in a polygonal pattern (spatial heterogeneity). This measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Currently, it is widely accepted that although variation in those organizations exist there is just a narrow range of variations of cellular polygonal distributions [34], [40]. In this regard, samples of polygonal mesh are directly comparable even if these meshes are from different nature or scales [49], [50] due to all of them are PSP, including biological natural images, biological simulations, non-biological simulations, such as random meshes and Poisson-Voronoi tessellations and random polygons. Therefore, levels of Shannon entropy in polygonal meshes and set of random polygons turns out into a window of universal and comparable information if we approach them from a pure geometric perspective.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, it is widely accepted that although variation in those organizations exist there is just a narrow range of variations of cellular polygonal distributions [34], [40]. In this regard, samples of polygonal mesh are directly comparable even if these meshes are from different nature or scales [49], [50] due to all of them are PSP, including biological natural images, biological simulations, non-biological simulations, such as random meshes and Poisson-Voronoi tessellations and random polygons. Therefore, levels of Shannon entropy in polygonal meshes and set of random polygons turns out into a window of universal and comparable information if we approach them from a pure geometric perspective.…”
Section: Methodsmentioning
confidence: 99%
“…At tissue level, we used images from proliferating Drosophila prepupal wing discs (dWP); [34], [45], [47], middle third instar wing discs (dWL); [45], [47], normal human biceps (BCA); [34], muscular dystrophy from skeletal muscles (MD); [46] and pseudo stratified Drosophila wing disk epithelium (PSD); [40]. Also, at the ecological level polygonal meshes derived from Namibia fairy circles (ecological patterns associated with SDCP convergences [49]) images were integrated into the analysis (NFC); [49], [50], [51]. The global tag to define MD, dWP, dWL, BCA, PSD and NFC is called BIO.…”
Section: Collecting Samples On Linementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, an important constraint in any spatial region may be the spatial homogeneity which we can understand as regularity and a statistical spatial organization argument of this constraint associated with FO is developed here. In a previous work, we considered quantitative spatial homogeneity among areas inside a region (a bounded polygon) as synonymous of regularity and the presence of disparity among areas as spatial heterogeneity [ 18 ]. Therefore, our definition of spatial heterogeneity is based on the unequal distribution of areas inside polygons; we propose a parameter to define quantitatively the spatial organization of inner polygonal elements around three main concepts: eutacticity, regularity and spatial heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our definition of spatial heterogeneity is based on the unequal distribution of areas inside polygons; we propose a parameter to define quantitatively the spatial organization of inner polygonal elements around three main concepts: eutacticity, regularity and spatial heterogeneity. It has been shown in a previous work [ 19 ] that eutacticity is a parameter closely linked with regularity and it is a suitable measurement of spatial homogeneity and heterogeneity [ 18 ]. Eutacticity is sharply linked with regularity by considering that a given polygon, polyhedron and, in general, polytope can be associated with a star of vectors (pointing from the center to the vertices) and it has been demonstrated that stars associated with regular polytopes are eutactic [ 20 ].…”
Section: Introductionmentioning
confidence: 99%